Audit Pada Akun Penjualan Real Estate PT RAI - Raa’fiuddin Al Ichlas; Anita Kusuma Dewi; Damayanti Damayanti (Jurnal Ilmiah ESAI, 2021)
PT RAI is a property company based in Jakarta.  Sales are the main activity of the company to increase revenue, the source of revenue comes from the sale of real estate.  There are constraints in recording sales that resulted in misstatements in 2019, this change occurred because the company could not fully acknowledge sales because there were sales that were not recognized by PSAK 72. The purpose of this writing is to know the audit process and the results of the audit of real estate sales accounts at PT RAI.   The source of data drafting this scientific work is secondary data with the method of data collection is a method of documentation and the analysis method used is quantitative descriptive. This article discusses the audit process of sales accounts that have been established by KAP TRR, based on the sales audit process conducted, the author notices some errors in the recognition of sales accounts.  In the final stages of examination conducted correction journal related to these errors.  Based on the discussion of this scientific work and the audit process that has been conducted at PT RAI, it can be concluded that the audit process on the sales account that has been done is sufficient. Audit adjustments have been made on the results of audit findings related to misstatements on sales accounts, then on the sales account there are no other material misstatements.